La bossa nova en France : un modèle musical ? - Anaïs Fléchet (Cahiers des Amériques Latines)
The success of bossa nova in France in the 1960’s and the 1970’s corresponds to an inversion and a diversification of the musical flows between Latin America and Europe. This article studies the musical exchanges between France and Brazil via the theory of «cultural transfers» – diffusion, reception, acculturation. It aims to demonstrate that a new Brazilian otherness was built in France during the 1960’s.